2014
DOI: 10.1007/s12013-014-0174-3
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Transplantation-Based Evolving Treatment Options in Spinal Cord Injury

Abstract: Spinal cord injury (SCI) often represents a condition of permanent neurologic deficit. It has been possible to understand and delineate the mechanisms contributing to loss of function following primary injury. The clinicians might hope to improve the outcome in SCI injury by designing treatment strategies that could target these secondary mechanisms of response to injury. However, the approaches like molecular targeting of the neurons or surgical interventions have yielded very limited success till date. In re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Currently, up to 30% of temporal lobe epilepsy patients have seizures despite treatment with antiepileptic drugs, either mono- or polytherapy, which result in physical harm to the patient and psychosocial dysfunction. This results in physiological damage in the forms of electrolyte imbalance, cerebral edema, congestive renal failure, refractory status epilepticus (SE), and sudden death [ 68 ] and also restricts their quality of life and performance in society [ 69 , 70 , 71 , 72 ]. Therefore, it is a priority to continue investigating the mechanisms underlying epilepsy to identify new targets and potential therapeutic agents for the treatment of this disorder.…”
Section: Epilepsy and Nrf2mentioning
confidence: 99%
“…Currently, up to 30% of temporal lobe epilepsy patients have seizures despite treatment with antiepileptic drugs, either mono- or polytherapy, which result in physical harm to the patient and psychosocial dysfunction. This results in physiological damage in the forms of electrolyte imbalance, cerebral edema, congestive renal failure, refractory status epilepticus (SE), and sudden death [ 68 ] and also restricts their quality of life and performance in society [ 69 , 70 , 71 , 72 ]. Therefore, it is a priority to continue investigating the mechanisms underlying epilepsy to identify new targets and potential therapeutic agents for the treatment of this disorder.…”
Section: Epilepsy and Nrf2mentioning
confidence: 99%
“…7 Stem cell transplantation is a promising candidate to treat SCI. [8][9][10][11][12] Recent work showed that stem cells, such as mesenchymal stem cells (MSCs), [13][14][15] neural stem/progenitor cells (NS/ PCs), 16,17 and embryonic stem cells (ESCs), [18][19][20] have immunoregulatory capacity and anti-inflammatory effects and could enhance functional improvement through inducing macrophages M1/M2 phenotype transformation post SCI. This review will discuss 1) the general feature of macrophages in response to SCI, 2) the phenotype and function of macrophages in SCI, and 3) the effects of stem cells on macrophage polarization and its role in stem cell-based therapies for SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality due to diabetes is more than 80% in the low and middle income countries ( 13 ). WHO predicts diabetes will be the 7th most important cause of mortality in 2030 ( 14 ) and in 2035 near to 592 million people will die due to diabetes ( 15 ).…”
Section: Introductionmentioning
confidence: 99%